A Phase II Study of a Dose-Density Regimen With Fluorouracil, Epirubicin, and Cyclophosphamide on Days 1 and 4 Every 14 Days With Filgrastim Support Followed by Weekly Paclitaxel in Women With Primary Breast Cancer. (30th January 2015) - Pietri, Elisabetta; Andreis, Daniele; Fabbri, Francesca; Menna, Cecilia; Schirone, Alessio; Kopf, Barbara; Rocca, Andrea; Amadori, Dino; De Giorgi, Ugo
Abstract: Author Summary: Background: Recent evidence shows that use of anthracycline and taxane adjuvant chemotherapy and dose-dense regimens, consisting of more frequent administration of the drugs, have improved outcomes for breast cancer patients. In this study, we evaluated administration of an epirubicin-based regimen with paclitaxel in a sequential, dose-dense schedule as adjuvant treatment for patients with high-risk primary breast cancer. Methods: In a phase II Simon two-stage design study, we evaluated the feasibility of a modified fluorouracil, epirubicin, and cyclophosphamide (FEC) regimen at high dose intensity (fluorouracil 500 mg/m 2 i.v. on days 1 and 4, epirubicin 60 mg/m 2 i.v. on days 1 and 4, and cyclophosphamide 500 mg/m 2 i.v. on days 1 and 4; all drugs were administered every 14 days for 3 cycles) with granulocyte colony-stimulating factor support followed by dose-intense weekly paclitaxel 100 mg/m 2 for 8 cycles. In 11 patients with breast cancer following quadrantectomy ( n = 8) or modified radical mastectomy ( n = 3), any grade 3 (G3) or higher nonhematologic toxicity (excluding alopecia, nausea or vomiting, and bone pain, which might be a consequence of the administration of filgrastim) and adherence to the scheduled dose-dense treatment (deliverability) were monitored with the purpose of enrolling an additional 27 patients in the case of a satisfying toxicity profile and deliverability of the planned treatment (at least 7 patients completing the treatment). Results: Five of 11 patients experienced G3 or higher nonhematologic toxicity during the FEC regimen. We did not observe G3 or higher nonhematologic toxicity related to paclitaxel treatment. In particular, three patients experienced G3 fatigue, one patient had G3 oral mucositis, three patients had G3 hypokalemia, one patient had G3 syncope, one patient had G3 transaminitis (alanine aminotransferase), one patient experienced G4 pulmonary thromboembolism, and 1 patient had a G3 breast infection. Four of 11 patients received the regimen with a 25% dose reduction of day 1 and 4 administrations of FEC. Seven of 11 patients required FEC delay ≥7 days in at least 1 cycle, regardless of dose intensity. Two patients failed to complete the FEC regimen. Two of the remaining 9 patients were treated with paclitaxel delay ≥7 days in at least one cycle. After a median follow-up of 28 months, 9 patients were continuously disease free. Conclusion: The tolerability rate of a dose-density regimen with FEC followed by weekly paclitaxel was considered not promising for completing the accrual of this study.